Analisis Rancangan Undang-Undang Perampasan Aset Dalam Sistem Pemerintahan Indonesia - Ahmad Dicky Arjunanda; Ibnu Nafi; Ahmad Nuzulurrizki; Yudi Widagdo Harimurti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The proposed Asset Seizure Bill has become urgent because the existing criminal justice system, as stipulated in the Corruption Eradication Law and the Money Laundering Law, has not been effective in recovering assets derived from crime, especially if the defendant dies, flees, or the criminal proceedings are halted. This study aims to analyze in detail the extent to which the Asset Seizure Bill can be integrated into the existing criminal and civil procedural law framework in Indonesia, as well as how a transparent and accountable mechanism for managing seized assets can be established for the recovery of assets in the public interest. The method used is normative legal research with a legal, conceptual, case, and comparative approach. The findings show that this bill adopts the mechanism of Asset Forfeiture Without Criminalization with an in-rem approach (targeting assets, not perpetrators) through civil court proceedings, as well as implementing the concept of unexplained wealth to expand the scope of forfeiture and close legal loopholes. The implication is that this bill is a strategic instrument in eradicating corruption and recovering state losses amounting to trillions of rupiah, but its success is highly dependent on careful formulation, ensuring due process of law, and the existence of political will and readiness of law enforcement officials.